Development of a large venous collateral after post-operative Ostial pulmonary vein atresia: An unusual clinical course. (December 2021) - Dalby, Stephen T.; Renno, Markus S.; Greiten, Lawrence E.; Reemtsen, Brian; Eisenring, Christian; Braden, Eric; Bornemeier, Renee; Zakaria, Dala
Abstract: Pulmonary vein obstruction after surgical repair of total anomalous pulmonary venous return is a known complication with particularly poor prognosis. A female infant developed left pulmonary vein atresia after obstructed supracardiac total anomalous pulmonary venous return repair. Over the first decade of life, a large venous collateral vessel draining the left pulmonary veins to the paraspinal venous plexus developed, enabling growth of the left pulmonary vasculature to low normal size and resulting in mild right heart dilatation from left-to-right shunting. Multimodality diagnostic imaging, including echocardiography, cardiac catheterization, cardiac CT, and 3D cardiac modeling aided in diagnosis and planning surgical correction of the left pulmonary venous drainage back to the left atrium. Unexpected right heart enlargement and growth of a branch pulmonary artery in the presence of ipsilateral pulmonary vein atresia following total anomalous pulmonary venous return repair should prompt further diagnostic investigation. In this case, the evaluation ultimately enabled surgical repair of this unique venous connection.